Análisis del empleo en los jóvenes del décimo semestre de la carrera de economía de la ULVR, para determinar la capacidad de emprendimiento en planes de negocios - Kure Camacho, Galo Christian (2016)
Entrepreneurship is one of the most significant activities, at present, for the emergence of new industries or complementary industries that create places of work and stimulate the economy of the countries. Such projects usually are developed by young people seeking to generate added value to already conceived ideas or find different ways to use traditional products. The conditions of the countries are key to the development of entrepreneurship, but this is not limited to that, only developed countries can provide such initiatives, because in developing country there are high rates of entrepreneurship through support provided by the government or private enterprise as loans, incentives, consulting, among others………..